PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI PUSAT STANDARDISASI INSTRUMEN KUALITAS LINGKUNGAN HIDUP (KLHK) - Rojali; Mulyani, Sri (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the influence of the work environment and organizational culture on employee performance at the Center for Standardization of Environmental Quality Instruments, partially or simultaneously. The method used is a quantitative method. The respondents used in this research were 62 respondents. The data analysis methods used in this research are validity test, reliability test, classical assumption test, multiple linear regression test, correlation coefficient test, coefficient of determination test, and hypothesis test using SPSS version 26 software. The results in this research are statistical results. t test shows a positive and significant influence of the work environment on employee performance. With a tcount value of 4.968 > ttable 2.001 or significant 0.000 < 0.05, thus there is a partial positive and significant influence of the work environment on employee performance. Then, the results of statistical tests show a positive and significant influence of organizational culture on employee performance. With a t value of 6.701 > t table 2.001 and a significant value of 0.000 < 0.05, thus there is a partial positive and significant influence of organizational culture on employee performance. And finally, the results of statistical calculations show a value of Fcount 23.411 > Ftable 3.153, using a significance limit of 0.05, the significance value is 0.000 < 0.05. Thus, H0is rejected and H3 is accepted. This means that there is a significant influence simultaneously between the work environment, organizational culture and employee performance at the Center for Standardization of Environmental Quality Instruments.